Financial Viability of Business Models For Engineered Vertical Hydroponics Systems For Sustainable Onion Production in The Philippines - Armas, Kenneth L.; Lorenzo, Engr. Gina; Cruz, Catherine Dela (Journal of Applied Engineering and Technological Science (JAETS), 2023)
This study aimed to explore the financial, socio-economic, and environmental benefits of sustainable onion production using vertical farming and hydroponic systems, and to identify key factors affecting the viability of these business models. Data were collected through a survey of onion farmers and producers in the Philippines, and analyzed using descriptive and inferential statistics. Results showed that sustainable onion production using vertical farming and hydroponic systems has the potential to generate higher income for farmers, increase employment opportunities, improve food security, enhance market competitiveness, and promote environmental sustainability. Key financial factors affecting viability included production costs, market prices, yield, labor costs, energy costs, capital costs, financing costs, taxes and regulatory costs, and maintenance and repair costs. Recommendations for optimizing financial viability include reducing production costs, diversifying income streams, and improving market competitiveness. Overall, this study suggests that sustainable onion production using vertical farming and hydroponic systems is a viable and promising approach to achieving socio-economic and environmental sustainability in the agricultural sector.